Dynamics of Theological Approaches in the Islamic Intellectual Tradition - Ikhsan, Arief Maulana; Mubaraq, Zulfi; Faishol, M.; Syuhadak, Syuhadak (Cakrawala: Jurnal Studi Islam, 2024)
This study investigates theological approaches within Islamic Studies, recognizing their dynamic and evolving nature. The research aims to: identify the predominant paradigms of theological inquiry within the field; analyze the internal and external factors influencing the emergence and development of these approaches; and assess the implications of these approaches for Islamic thought and practice. Employing a descriptive qualitative methodology and a literature review approach, the study reveals three primary theological paradigms: historical, normative, and dialogical. Internal factors, such as belief systems, commitment levels, and scholarly loyalties, significantly shape these approaches. External factors, including language, cultural contexts, and diverse sources of knowledge, further contribute to their diversity. The findings suggest that theological approaches in Islamic Studies can positively impact belief systems, foster religious tolerance, and encourage critical, dialectical thinking. However, limitations in the scope of this study necessitate further in-depth research to fully comprehend the multifaceted nature of theological approaches within Islamic Studies.